Building students’ WASAKA character and muscle strength through the integration of the direct instruction model and practice style - Herita Warni; Mashud Mashud; Muhammad Fadillah; Pebriyandi Pebriyandi (Jurnal Cakrawala Pendidikan, 2026)
Physical education plays a strategic role in shaping students' character and physical, but practices in the field are still largely dominated by conventional approaches that are less effective in optimally instilling values of resilience. The local value of “WASAKA” (Waja Sampai Kaputing), which reflects a never-give-up attitude, discipline, and responsibility, is considered relevant to be integrated into physical education learning to strengthen students' character in facing contemporary challenges. This study aims to examine the effectiveness of integrating the Direct Instruction and Practice Style models in fostering the WASAKA attitude and improving the muscle strength of elementary school students. The study employed a quantitative approach using a quasi-experimental pretest–posttest control group design, involving 80 students from two elementary schools in Banjar Regency who were divided into experimental and control groups. The instruments used included a WASAKA attitude questionnaire and muscle strength tests consisting of push-ups, sit-ups, and vertical jumps. Data were analyzed using descriptive statistics, normality and homogeneity tests, as well as inferential statistical tests, including the paired t-test, Wilcoxon test, independent t-test, Mann–Whitney test, and simple linear regression. The results revealed a significant increase in both WASAKA attitude scores and muscle strength among students in the experimental group compared to those in the control group (p < 0.05). However, the linear regression analysis indicated that there was no statistically significant relationship between WASAKA attitude and students’ muscle strength (p > 0.05). In conclusion, the integration of the Direct Instruction and Practice Style models proved effective in improving physical education learning outcomes in terms of both character development and physical fitness, although the two variables did not directly influence one another. This model is therefore recommended as an innovative learning approach to support the integrated development of students’ character and physical fitness.